Influence of Supply Chain Factors on Reshoring Decisions – A Structured Literature Review - Daniella FJELLSTROM; Ehsanul CHOWDHURY; Tawhidul ISLAM; Sharif AHMED (Communications of International Proceedings, 2023)
Aim: The purpose of this study is to explore how supply chain factors that influence decisions on reshoring have been discussed in previous research.  Methodology: A structured literature review is used to analyze 139 peer-reviewed articles containing reliable and effective arguments and discussion related to the aim of the study, retrieved from the online research databases of EBSCOhost, Science Direct, Emerald Insight and Springer.  Findings: The study identifies four supply chain factors that influence reshoring decisions, namely: supply chain resources, supply chain reconfiguration, the customer-supplier relationship, and supply chain proximity.  Implications of the study: This study provides a novel starting point from which future researchers can initiate empirical studies to evaluate the influence of the identified supply chain factors on reshoring decisions. The findings can, in addition, help practitioners and managers to develop knowledge of the influence of supply chain factors when making reshoring decisions.   Originality – This structured review extends our knowledge on the link between supply chain factors and reshoring, by drawing attention to how the factors of supply chain resources, supply chain reconfiguration, the customer-supplier relationship, and supply chain proximity influence reshoring decisions.
Keywords: Resources; configuration; relationship; proximity; challenges; networks